Short-term NO2 exposure and cognitive and mental health: A panel study based on a citizen science project in Barcelona, Spain. (June 2022) - Gignac, Florence; Righi, Valeria; Toran, Raül; Paz Errandonea, Lucía; Ortiz, Rodney; Mijling, Bas; Naranjo, Aytor; Nieuwenhuijsen, Mark; Creus, Javier; Basagaña, Xavier
Graphical abstract: Highlights: Recent nitrogen dioxide (NO2 ) exposure is associated with stress and sleep quality. Short-term NO2 exposure is associated with selective attention. Proximity to natural spaces may modify the association between NO2 and attention. Abstract: Background: The association between short-term exposure to air pollution and cognitive and mental health has not been thoroughly investigated so far. Objectives: We conducted a panel study co-designed with citizens to assess whether air pollution can affect attention, perceived stress, mood and sleep quality. Methods: From September 2020 to March 2021, we followed 288 adults (mean age = 37.9 years; standard deviation = 12.1 years) for 14 days in Barcelona, Spain. Two tasks were self-administered daily through a mobile application: the Stroop color-word test to assess attention performance and a set of 0-to-10 rating scale questions to evaluate perceived stress, well-being, energy and sleep quality. From the Stroop test, three outcomes related to selective attention were calculated and z-score-transformed: response time, cognitive throughput and inhibitory control. Air pollution was assessed using the mean nitrogen dioxide (NO2 ) concentrations (mean of all Barcelona monitoring stations or using location data) 12 and 24 h before the tasks were completed. We applied linear regression with random effects by participant to estimate intra-individual associations, controlling for day of the week and time-varying factors such as alcohol consumption and physical activity. Results: Based on 2, 457 repeated attention test performances, an increase of 30 μg/m 3 exposure to NO2 12 h was associated with lower cognitive throughput (beta = −0.08, 95% CI: −0.15, −0.01) and higher response time (beta = 0.07, 95% CI: 0.01, 0.14) (increase inattentiveness). Moreover, an increase of 30 μg/m 3 exposure to NO2 12 h was associated with higher self-perceived stress (beta = 0.44, 95% CI: 0.13, 0.77). We did not find statistically significant associations with inhibitory control and subjective well-being. Conclusions: Our findings suggest that short-term exposure to air pollution could have adverse effects on attention performance and perceived stress in adults.